Regional Economic Outlook, April 2007, Western Hemisphere. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2007)
The past year has been one of strong economic performance for the Western Hemisphere, notwithstanding somewhat slower growth in the United States in recent quarters. Can this performance be sustained, and what challenges does the region face? Reviewing macroeconomic prospects and risks, this report pays particular attention to the influence of the external environment on Latin America, and addresses the question of whether Latin America has now succeeded in breaking with its history of periodic growth reversals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet